2021
DOI: 10.3390/app11125366
|View full text |Cite
|
Sign up to set email alerts
|

Robo-HUD: Interaction Concept for Contactless Operation of Industrial Cobotic Systems

Abstract: Intuitive and safe interfaces for robots are challenging issues in robotics. Robo-HUD is a gadget-less interaction concept for contactless operation of industrial systems. We use virtual collision detection based on time-of-flight sensor data, combined with augmented reality and audio feedback, allowing the operators to navigate a virtual menu by “hover and hold” gestures. When incorporated with virtual safety barriers, the collision detection also functions as a safety feature, slowing or stopping the robot i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Head pose estimation from a single image is a key task in facial analysis that is used for a wide range of applications such as driver assistance [1], augmented reality [2], and human-robot interaction [3]. Current methods are commonly divided into landmark-based and landmark-free approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Head pose estimation from a single image is a key task in facial analysis that is used for a wide range of applications such as driver assistance [1], augmented reality [2], and human-robot interaction [3]. Current methods are commonly divided into landmark-based and landmark-free approaches.…”
Section: Introductionmentioning
confidence: 99%
“…→ 1 : m 34 Figure: [131] - [13, 48, 78, 90, 101, 107, 131, 142, 145, 163, 176-178, 212, 235, 240, 246, 248, 263, 265, 284, 301, 306, 327, 328, 340, 344, 387, 388, 391, 395, 416, 425, 448] → n : 1 25 Figure: [430] - [10,31,77,91,112,146,159,166,168,275,317,320,338,343,345,364,369,382,404,410,418,430,436,461,475] → n : m 10 Figure: [328] - [71,200,221,328,375,408,412,415,431,451] Scale → Handheld-scale 19 Figure: [179] - [39,46,71,86,179,237,238,258,…”
Section: Discussionmentioning
confidence: 99%
“…As Pasinetti et al [9] have shown, time-of-flight (ToF) cameras can be used to detect the operator and, in combination with virtual barriers, slow or stop the robot when safety guidelines are infracted. In addition, one of our previous implementation of a gadget-less HRI concept Robo-HUD suggests that a non-contact approach also contributes to a safe HRI [10]. An attention module based on head posture estimation was introduced to monitor attention, allowing intended user actions.…”
Section: Related Workmentioning
confidence: 99%